FORMULASI BISKUIT DENGAN SUBSTITUSI TEPUNG IKAN LELE DUMBO (Clarias gariepinus) DAN ISOLAT PROTEIN KEDELAI (Glycine max) SEBAGAI MAKANAN POTENSIAL UNTUK ANAK BALITA GIZI KURANG [Biscuit Formulation with Catfish Dumbo (Clarias gariepinus) Flour and Soy (Gl - . Mervina; Clara M. Kusharto; Sri Anna Marliyati (Jurnal Teknologi dan Industri Pangan, 2012)
Fish is a protein source important for enhancing nutritional status because it is categorized as high quality food. Fish flour is one of the fish product that has not been optimally utilized as food. The objective of this research was to produce biscuit formulated with Dumbo catfish (Clarias gariepinus) flour and soy protein isolate, as a high protein food for undernourished under-five years old children. The purpose of soy protein isolate substitution was also to produce better biscuit texture. Fish flour was made separately from body and head part, and then was analyzed for its physical and chemical properties. Biscuits were formulated by substitution of fish flour and soy protein isolate with trial and error method. A selected formula was determined based on semi trained panelists preference. Acceptance of the biscuit made with the selected formula was examined by children and children’s mothers using hedonic test. The contribution of protein contained in biscuit on daily allowance was calculated for under-five year old children. Biscuits made by substitution of 3.5% of body fish flour, 1.5% of head fish flour, and 10% of soy protein isolate was the preferred formula. The chemical properties for biscuit of the accepted formula (F4) were as follows: 3.96% (wb) of water content, 2.52% (db) of ash content, 19.55% (db) of protein content, 21.99% (db) of fat content and 55.94% (db) of carbohydrate content (by different). The biscuit contains 480 Kcals energy per 100 grams. The protein digestibility of the biscuit measured by enzymatic method was 89.34%. The formula fulfills 20% of children’s protein needed per day from four pieces of biscuit or equals to 50 grams of biscuit.